Pengaruh Kepuasan Pernikahan terhadap Kepuasan Hidup Pasien Kanker Dewasa Muda - Chantika, Shelly; Sutanto, Sandra Handayani (Jurnal Online Psikogenesis, 2023)
Cancer diagnoses are affecting physical health as well as someone’s mental health, especially in young-adult patients who’s on a phase to build their career and family. The purpose of this study is to understand the influence of marital satisfaction on life satisfaction among cancer patients in young adulthood (20-40 years old) in Jakarta. This research is quantitative research with correlational study design with linear regression analysis. A total of 31 participants took part in this study and were collected through convenience sampling. This study uses self report questionnaire with Relationship Assesment Scale (α = 0.84) and Satisfaction with Life Scale (α = 0.88). This study states that there is a significant influence of marital satisfaction through deep love and more support from partners to their life satisfaction among young adult cancer patients (R2= 0,499, F (1,29) = 28,930, p<0,01).